RAISING QUALIFICATION OF ENGINEERING PERSONNEL: ORGANIZATIONAL NOVATIONS AND EDUCATIONAL TECHNOLOGIES - Vasyliy G. Ivanov; Svetlana V. Barabanova; Olga Yu. Khatsrinova (Высшее образование в России, 2016)
The article is devoted to conditions of the realization of the Presidential Program for training engineering staff for 2012-2014. The authors reveal the problems of implementing the additional educational programs for engineering personnel such as alienation from the real practice, interdisciplinary approach ignoring, neglect of students’ personal professional and social experience and others. So, this is the reason for development of innovative strategies for additional vocational training in conditions of public-private partnership and forconstructing a system of listeners’ scientific and methodological support. There is proposedthe theoretical substantiation of the model of interdisciplinary integrated training of engineering staff within the framework of the system of additional vocational education and skills upgrading.